1989
DOI: 10.1093/ajcn/49.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive weight loss and weight regain: effects on weight reduction, resting metabolic rate, and lipolytic activity before and after exercise and/or diet treatment

Abstract: Body composition, maximal aerobic power (VO2 max), resting metabolic rate (RMR), and lipolytic activity of abdominal adipocytes were measured in 20 women (body mass index [BMI] = 33.5) during 14 wk of exercise training (4 h/wk at 60% of VO2 max) and dietary restriction (840 kcal/d). Frequent dieters (yo-yo) and women without a dietary history (non-yo-yo) were matched into the following groups: diet-exercise yo-yo (DE-Y), diet-exercise non-yo-yo (DE-NY), and diet-non-yo-yo group (D-NY). After 14 wk significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…The other lifestyle approach, that is, energy restriction, has been shown to be an effective treatment of obesity in the short term (Van Dale & Saris, 1989;Kempen et al, 1995;Pasman et al, 1999). On a group level, weight loss can be successful by either energy restriction (Van Dale & Saris, 1989;Kempen et al, 1995;Pasman et al, 1999) or exercise (Ross et al, 2000;Fogelholm & Kukkonen-Harjula, 2000;Garrow & Summerbell, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other lifestyle approach, that is, energy restriction, has been shown to be an effective treatment of obesity in the short term (Van Dale & Saris, 1989;Kempen et al, 1995;Pasman et al, 1999). On a group level, weight loss can be successful by either energy restriction (Van Dale & Saris, 1989;Kempen et al, 1995;Pasman et al, 1999) or exercise (Ross et al, 2000;Fogelholm & Kukkonen-Harjula, 2000;Garrow & Summerbell, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…On a group level, weight loss can be successful by either energy restriction (Van Dale & Saris, 1989;Kempen et al, 1995;Pasman et al, 1999) or exercise (Ross et al, 2000;Fogelholm & Kukkonen-Harjula, 2000;Garrow & Summerbell, 1995). Contrarily, on a group level, successful long-term weight maintenance, either with energy restriction, prescribed exercise, or diet and exercise has hardly been shown (Van Dale & saris, 1989;Froidevaux et al, 1993;Hensrud et al, 1994;Muls et al, 1995;Fogelholm et al, 1999;Pasman et al, 1999). However, on the individual level, differences in successful weight maintenance after an energy restriction period have been shown to be related to increases in cognitive restrained eating behaviour during the energy restriction phase (Clark et al, 1994;Hensrud et al, 1994;Pekkarinen et al, 1996;WesterterpPlantenga et al, 1998;Fogelholm et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the relationship between fluctuations in body weight and a variety of disease markers has been examined retrospectively using several large data bases. Weight fluctuations are associated with increased risk of disease in some data bases (18,28,30), but not in others (26,29,36,41). Wing (44) provides an excellent review of the human literature, concluding that weight cycling has no consistent effects on a number of metabolic variables, but may be related to mortality and cardiovascular morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that weight variability affects body composition by increasing total body fat has been denied in all studies, 8,[11][12][13][14] except one.15) Regarding energy expenditure, some found that weight variability decreases resting metabolic rate,11,15) but others reported negatively. 8,13,16) Although many long-term studies have observed an association of weight variability with negative health consequences, studies investigating the mechanism of the effects have failed to show a causal relationship.…”
mentioning
confidence: 99%
“…8,13,16) Although many long-term studies have observed an association of weight variability with negative health consequences, studies investigating the mechanism of the effects have failed to show a causal relationship. One explanation for this is that, in most studies, information on weight variability was based on each subject's recall and may therefore have been misclassified.…”
mentioning
confidence: 99%